2020
DOI: 10.1002/ijgo.13387
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity before and during pregnancy: A cohort study

Abstract: Objective To estimate physical activity (PA) in healthy women before and during pregnancy and to evaluate the features associated with moderate PA (MPA). Methods A prospective cohort study was conducted on women selected 14 weeks of pregnancy during 2013–2015 in primary public health service centers in southern Spain. Type, duration, and frequency of PA (IPAQ questionnaire in first, second, and third trimesters [T1, T2, T3]) were measured. Variables associated with MPA were evaluated using multiple logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 26 publications
(42 reference statements)
5
31
1
1
Order By: Relevance
“…This is in line with previous evidence that suggested that physical activity levels decrease along gestation [27]. In particular, it has been shown [24] that between the second and the third trimester of pregnancy, there was a decrease in physical activity (assessed with the International Physical Activity Questionnaire), which is highly in agreement with our findings. In this regard, the high prevalence of overweight and obesity prior to pregnancy and the decreasing time spent in total physical activity might imply a higher cardiometabolic risk in this population [1,28,29].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in line with previous evidence that suggested that physical activity levels decrease along gestation [27]. In particular, it has been shown [24] that between the second and the third trimester of pregnancy, there was a decrease in physical activity (assessed with the International Physical Activity Questionnaire), which is highly in agreement with our findings. In this regard, the high prevalence of overweight and obesity prior to pregnancy and the decreasing time spent in total physical activity might imply a higher cardiometabolic risk in this population [1,28,29].…”
Section: Discussionsupporting
confidence: 94%
“…Regarding pre-pregnancy body composition of the study sample (pre-pregnancy BMI (23.2 kg/m 2 )), it was similar to that observed by Martin et al [1] in which pregnant women with the highest adherence (Tertile 3) to the Dietary Approaches to Stop Hypertension score-based method had a prepregnancy BMI of 22.8 kg/m 2 [1]. In addition, a recent study [24] conducted in Spain reported that 37% of pregnant women were overweight/obese prior to pregnancy, similar to our results (35%). Comparing the early second trimester (16th g.w.)…”
Section: Discussionsupporting
confidence: 83%
“…Both the WHO and the American College of Obstetricians and Gynecologists recommended 150 minutes moderate physical activity per week for all healthy pregnant women 9,10 . However, research has found that physical activity in women decreases from prepregnancy to pregnancy 11,12 . In fact, the majority of pregnant women do not meet the recommended amount of duration for daily physical activity 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“… Sociodemographic, psychosocial, anthropometric and pregnancy variables [ 55 ] Rêgo 2017 Brazil Cohort study 1447 Nulliparous pregnant women 25–26 wk IPAQ MET min/wk No association was found between the level of PA in the 2T and 3T with adverse perinatal outcomes. Sociodemographic, pregnancy and delivery variables [ 56 ] Román-Gálvez 2021 Spain Prospective cohort study 463 Healthy pregnant women 1T: <14 wk 2T: 24 wk 3T: >32 wk IPAQ MET min/wk Two-thirds of women achieve enough PA. Energy expenditure decreases throughout pregnancy. Sociodemographic, behavioral anthropometric and pregnancy variables.…”
Section: Methodsmentioning
confidence: 99%